Mechanical behavior and deformation mechanisms of Mg–5Y alloy under dynamic compressive impact - Kang Wei; Yonghao Zhao; Lirong Xiao; Yazhou Guo; Yi Liu; Lei Li; Dongdi Yin; Hao Zhou (Journal of Materials Research and Technology)
The dynamic mechanical behaviors of magnesium alloy components assume paramount importance owing to its involvement in high-speed deformation during the forming process or in extreme service conditions. However, an in-depth exploration of the microscopic deformation mechanisms of rare earth magnesium alloys under high strain rates remains relatively scant, especially concerning the intricate relationship between microstructure evolution and dynamic mechanical properties. In this work, we investigate the dynamic compressive properties of extruded fine-grained Mg–5Y alloy subjected to high strain rates ranging from 800 to 2000 s−1, employing Hopkinson impact experiments. We find an enhancement in yield strength from 165 MPa at 800 s−1 to 208 MPa at 2000 s−1, while the compressive strain reaches to 0.21 at 2000 s−1. The calculated strain rate sensitivity factor, denoted by 'm', registers at 0.00795, exhibiting a subdued strain rate sensitivity. Notably, the absence of adiabatic shear bands in the samples attests to their high work hardening capacity, and the ultimate compressive strength reaching an impressive 519 MPa at 2000 s−1. An accelerated strain hardening appears at the middle stage of deformation. A modified constitutive equation tailored for high strain rate deformation at ambient temperatures is established, based upon the Johnson-Cook model. Detailed microstructural analyses reveal that the deformation mechanisms are dominated by deformation multiple twinning, basal dislocations, non-basal dislocations and I1 stacking faults, collectively supporting the high-level strain hardening behavior in Mg–5Y alloys. Our work provides comprehensive insights for the effective utilization of magnesium alloys in high-speed deformation conditions within industrial applications.